Corporate Social Responsibility in Saudi Arabia Service Sector A Qualitative Analysis - Luísa PINTO (Communications of International Proceedings, 2021)
Private and public organizations are receiving more and more attention from numerous stakeholders for their social performance, which includes not only issues of how they treat their workers and communities where their operations are located, but increasingly they are asked about the social profile of their suppliers and how they treat their workers and communities in which they operate. The response of businesses and public organizations to this attention is diverse, ranging from developing internal policies and putting demands on suppliers, to philanthropy projects, working directly with suppliers on aspects of labor practices or engaging in activities ensuring human rights in supply chains. The purpose of this study is to identify the social practices in Saudi Arabia service sector and the relationship between these practices and company performance. The study was based on the data collected from 8 semi-structured interviews with human resources managers, and managers, and procurement and environmental/safety managers, and through secondary data collected from reports, websites and companies' internal documentation. The analysis identifies the most important social practices considered by managers, as well as the performance measures that are most appropriate and most widely used to evaluate. This study will contribute to the body of knowledge in the area of corporate social responsibility in Saudi Arabia. The results can be used by managers through the adoption of certain social practices to improve their performance.
Keywords: Social Responsibility; Drivers; Barriers; Benefits; Saudi Arabia